2013
DOI: 10.2489/jswc.68.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of vegetation recovery on runoff and soil erosion on a Wenchuan earthquake-triggered landslide, China

Abstract: Abstract:In order to find suitable vegetation types for wider earthquake-triggered landslide rehabilitation in the eastern Longmenshan, we chose six vegetation types, which included three artificial restoration vegetation types (shrub Paeonia decomposita, deciduous tree Betula albo-sinensis, and evergreen tree Cryptomeria fortunei), two natural restoration vegetation types (middle and high coverage of grasses), and one residual vegetation. Soil quality, runoff, and soil loss were evaluated for the six vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The peak flow discharge reduced by 2.15% and the base flow increased by 0.34%. This result is consistent with the finding of Fusun et al (2013) who found a high coverage of grasses prevents surface runoff and soil erosion more effectively. This is due to the fact that grasses have the ability to reduce the rain drop impact on soils, to increase infiltration rate, and to reduce surface runoff volume by reducing the velocity of the runoff and give time to infiltrate to the sub surface.…”
Section: Scenario1supporting
confidence: 93%
“…The peak flow discharge reduced by 2.15% and the base flow increased by 0.34%. This result is consistent with the finding of Fusun et al (2013) who found a high coverage of grasses prevents surface runoff and soil erosion more effectively. This is due to the fact that grasses have the ability to reduce the rain drop impact on soils, to increase infiltration rate, and to reduce surface runoff volume by reducing the velocity of the runoff and give time to infiltrate to the sub surface.…”
Section: Scenario1supporting
confidence: 93%
“…An investigation in 1999 and 2005 by ICIMOD and its partners showed that there were 8790 glacial lakes covering a total of 801.83 km 2 in the HKH, of which 203 lakes were potentially dangerous and could pose a GLOF threat in the future (Ives et al 2010). As vegetation development is a slow process at such high altitudes, these sites may remain unprotected against erosion for decades or even centuries (Fusun et al 2013). Landslides and debris flows thus pose long-term threats to settlement and infrastructure in many places.…”
Section: Impact Of Mountain Hazards Amplifiedmentioning
confidence: 99%
“…Having a slightly different aim from that of our study, Fusun et al (2013) sought alternatives to rehabilitate areas after landslides in China, for which they tested six different plant covers. The authors evaluated soil quality, soil loss and surface runoff.…”
Section: Gross Precipitationmentioning
confidence: 99%